2008
DOI: 10.1128/mmbr.00031-07
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Evolution of Bacterial ATP-Binding Cassette Systems

Abstract: SUMMARY ATP-binding cassette (ABC) systems are universally distributed among living organisms and function in many different aspects of bacterial physiology. ABC transporters are best known for their role in the import of essential nutrients and the export of toxic molecules, but they can also mediate the transport of many other physiological substrates. In a classical transport reaction, two highly conserved ATP-binding domains or subunits couple the binding/hydrolysis of ATP to the transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
1,157
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,185 publications
(1,187 citation statements)
references
References 564 publications
(669 reference statements)
15
1,157
0
15
Order By: Relevance
“…The structural foundations for this analysis are most advanced for Type I importers, 10 particularly for the maltose MalFGK 2 transporter, [25][26][27][28] and provide an important framework for interpreting the mechanistic significance of the current MetNI structures. Structurally characterized type I importers include MalFGK 2 in outward facing (PDB IDs 2R6G 13 and 3PUY 27 ), pretranslocation (PDB IDs 3PV0 and 3PUZ 27 ), and inward facing (3FH6 36 ) conformations, ModABC in the inward and inward/inhibited conformations (PDB IDs 2ONK 24 and 3D31, 32 respectively), and the CY5 and DM forms of MetNI (PDB IDs 3TUI and 3TUJ, respectively) presented in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural foundations for this analysis are most advanced for Type I importers, 10 particularly for the maltose MalFGK 2 transporter, [25][26][27][28] and provide an important framework for interpreting the mechanistic significance of the current MetNI structures. Structurally characterized type I importers include MalFGK 2 in outward facing (PDB IDs 2R6G 13 and 3PUY 27 ), pretranslocation (PDB IDs 3PV0 and 3PUZ 27 ), and inward facing (3FH6 36 ) conformations, ModABC in the inward and inward/inhibited conformations (PDB IDs 2ONK 24 and 3D31, 32 respectively), and the CY5 and DM forms of MetNI (PDB IDs 3TUI and 3TUJ, respectively) presented in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic understanding of the transporter cycle is most advanced for Type I importers, particularly the maltose MalFGK 2 importer, where a combination of biochemical, biophysical, and structural studies have provided important insights. [25][26][27][28] These studies have revealed a range of conformational states corresponding to inward and outward facing stabilized with various nucleotides, binding proteins, and mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence comparison analyses allowed the assignment of UvrA to the ATP binding cassette (ABC) ATPase superfamily (Pfam code: PF09818), whose members are involved in many different cellular functions, ranging from import/export transport across the membranes to non-transport-related phenomena, DNA repair among these (15). …”
Section: Introductionmentioning
confidence: 99%
“…ATP-binding cassette transporters (ABC transporters) utilize the energy of ATP binding and hydrolysis to transport various substrates across cellular membranes. Bacterial ABC transporters and secretion systems are essential in cell viability, virulence, and pathogenicity [33,34]. Seven subclasses of ABC transporter proteins were identified in Pf1 based on different substrates.…”
Section: Phylogenetic Analysis and Genotypingmentioning
confidence: 99%